The fast-recycling receptor Megalin defines the apical recycling pathway of epithelial cells - Andres E. Perez Bay (Nature Portfolio, 2016)
Basolateral recycling and transcytotic pathways in epithelial cells are defined by specific markers, however the apical recycling pathway is poorly understood. Perez Bay et al. show that Megalin is a marker for this pathway, which intersects with the other routes in shared perinuclear recycling endosomes.